2003
DOI: 10.1046/j.1365-2702.2003.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pain and health‐related quality of life between two groups of cancer patients with differing average levels of pain

Abstract: A study was performed to describe and compare pain and Health-Related Quality of Life (HRQOL) in two groups of cancer patients in palliative care as well as to describe the correlation between pain and HRQOL. ○ Forty-seven patients with mild average pain [Visual Analogue Scale (VAS) < 3] and 28 patients with moderate to severe average pain (VAS > 3) were included. Medical Outcomes Study Short Form (SF-36) was used to evaluate HRQOL, pain intensity levels were measured with the VAS on Pain-O-Meter. ○ Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
2
22
0
5
Order By: Relevance
“…Relations between specific components of symptoms have not been discussed in the emerging symptom cluster literature. For example, pain was an independent predictor of QoL in two of our multivariate models, which is consistent with previous findings (Boström et al 2003;Borglin et al 2005). Pain in patients with advanced cancer is a multidimensional concept, comprising both physical and psychological aspects (Cleeland et al 1996), and varies with physical activity.…”
Section: Symptom Clusterssupporting
confidence: 92%
“…Relations between specific components of symptoms have not been discussed in the emerging symptom cluster literature. For example, pain was an independent predictor of QoL in two of our multivariate models, which is consistent with previous findings (Boström et al 2003;Borglin et al 2005). Pain in patients with advanced cancer is a multidimensional concept, comprising both physical and psychological aspects (Cleeland et al 1996), and varies with physical activity.…”
Section: Symptom Clusterssupporting
confidence: 92%
“…The underlying mechanism is unknown, but appetite and satiety controls are mediated by a complicated interplay of neuroendocrine signaling pathways involving a great variety of peptide hormones and neuropeptides, including ghrelin and PYY 3À36 (Romijn et al, 2008) Although appetite-stimulating plasma ghrelin concentrations decrease after gastrectomy, appetite would not have been changed due to compensation of other hormones involved in the control of appetite and food intake. Positive emotions to overcome the cancer in patients with gastric cancer who underwent gastrectomy may positively influence the subjective VAS appetite ratings 1 year after surgery (Boström et al, 2003). We reported that compensatory ghrelin production occurred in the remnant stomach after the surgical removal of part of the stomach as well as other tissues or organs such as the bowel, pancreas, kidney and placenta in postoperative day 7 (Jeon et al, 2004).…”
Section: Jeon Et Al 2004mentioning
confidence: 95%
“…[7][8][9]31,32 NP, as part of the neurological disease spectrum, is a common disability and expresses serious medical pathology. Apart from traumatic nerve injury, numerous diseases may be accompanied by NP.…”
Section: Epidemiologymentioning
confidence: 99%
“…Similarly to all intractable pains, it has devastating consequences on the overall quality of life; not only it deranges patients' ability to perform daily functions and their ability to manage their disease, but it also amplifies the anxiety and the distress of the affected patient and family. [7][8][9] NP is commonly presented in cancer patients and is considered a well-established entity for more than 20 years. Approximately, 1/3 of cancer patients experience NP, usually mixed with nociceptive components, or, occasionally, as a single, autonomous entity.…”
mentioning
confidence: 99%